2020
DOI: 10.2147/rmhp.s247774
|View full text |Cite
|
Sign up to set email alerts
|

<p>Review of Health Economics of Point-of-Care Testing Worldwide and Its Efficacy of Implementation in the Primary Health Care Setting in Remote Australia</p>

Abstract: There are important differences concerning health outcomes between the Australian population living in rural/remote regions and the urban population. Health care provision in remote areas, particularly in regions with a low number of inhabitants, is not without challenges. Aboriginal, rural and remote communities are therefore affected, as they face various obstacles in accessing health services, owing to geographical settings, difficulties in transportation to nearby hospitals, limited or inexistent local qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…This is particularly valuable to those living in rural and regional areas with limited access to healthcare services. 39 , 40 The use of urate self‐monitoring devices (alongside apps and support from healthcare providers) at home has been shown to be convenient, improve understanding, and communication. 41 Further, the inability to self‐monitor at home, or if the device was too expensive, would prevent frequent monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly valuable to those living in rural and regional areas with limited access to healthcare services. 39 , 40 The use of urate self‐monitoring devices (alongside apps and support from healthcare providers) at home has been shown to be convenient, improve understanding, and communication. 41 Further, the inability to self‐monitor at home, or if the device was too expensive, would prevent frequent monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Despite POCTs being considered especially beneficial to resource-limited health systems of LMICs, this study, in line with others, shows their use to be appreciated also in a wellresourced context, despite high accessibility to more advanced laboratory diagnostics and skilled personnel. [4,5,7,8,[20][21][22][23] POCTs are often less invasive and require smaller volumes of patient specimens than central laboratory facilities, which, together with their evolving multiplexity, promotes their use in paediatric clinics. [2,24] In our study, POCTs were merited as facilitators of patient management by accelerating differential diagnostics and patient flow at the PED, being favourable to paediatric clientele and essential to the emergency department setting of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the United Kingdom, a primary care study also reported that POC testing was cost effective, in comparison to laboratory testing, when used to perform routine health checks as the results were available at the first consultation [33]. A review of POC testing health economics in remote primary health care settings also provided general support for POC testing benefits to health services outweighing the associated costs [35]. In Australia, the Medical Services Advisory Committee (MSAC), is an independent, non-statutory committee established by the Minister for Health, that is responsible for the appraisal of new medical services proposed for public funding, including POC testing.…”
Section: Economic Outcomesmentioning
confidence: 99%